(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
The study aimed to recognize the level of the psychological stress that parents of mentally handicapped children suffer from and its relation with their coping styles. The sample of the study consisted of (30) parents divided into (12) fathers and (18) mothers who all have children with low or moderate levels of mental handicap in Sweida City. The researcher uses the standard of psychological stress of the parents of the handicapped children and the standard of coping styles with the psychological stress. Both standards are made by Saratawi and Al- Shaks (1998). The study has the following conclusions: -The level of the psychological stress of the sample studied appears to be moderate. -The order of the sample studied concerning the coping styles from the most preferable to the least is as the following: The specialist knowledge practices, the public knowledge practices, the ideological and sentimental practices, the escape practices, and the mixed practices. -There is a statistical significant positive correlation between coping styles and psychological stress. - There are no statistical significant differences in the level of psychological stress concerning the gender variable of the parents. But there are statistical differences concerning the variable of the degree of the child’s handicap. -There are no statistical significant differences in coping styles according to the gender variable of the parents, while there are statistical significant differences in coping styles which are based on escape practices and mixed practices and that is according to the variable of the level of the mental handicap in the favor of moderate level. Moreover, there are no statistical significant differences in the other styles of copping in the total degree.